The self-coordinated computation of electronic power spectrum and wave function in crystals with type structure to diamond - Sobchuk, Igor; Rakobovchuk, Larisa; Мischyshyn, Volodymir (Видавництво Національного університету "Львівська політехніка", 2002)
The calculations of self-coordinated power spectrum in the basic high symmetrical зБ ГL and ГХ directions are stated in this article. Because the germanium has a lesser width of forbidden zone in comparison by silicon, that approximates it to metals, then influence of correlation effects becomes prettily perceptible. That's why attached to Е(к) calculations of germanium the correlation amendments are included into crystalline potential. The analysis of results calculations shows, that an increasing of base length to 331 ПХ brings to energy values stabilization, which are close to experimental.
Keywords: crystals; structure; power spectrum; wave function